Private Universities and Building a World Class University in Africa (Global Journal of Human-Social Science, 2021)
In the past decade, the term "world-class university" "WCU" -also called "globally competitive universities", "world-class", "elite", or "flagship" universities-has become a catch phrase, not simply for improving the quality of learning and research in higher education but also, more important, for developing the capacity to compete in the global higher education marketplace through the acquisition and creation of advanced knowledge. This paper will provide a description of the attributes of world-class universities, the steps in building and sustaining world-class universities in Africa and will propose methodologies by which private universities in Africa can attain world-class status sharing the experiences in Nigeria. The paper will be concluded to offer a few tips to private Universities to guide their earnest quest to attain world-class status.